Sulla terzina dantesca. Una lezione liceale - Blasucci, Luigi (L’ospite ingrato, 2021)
In memory of Luigi Blasucci (1924-2021), we propose his beautiful «high-school lesson» on Dante’s tercet, held at Pisa, Scuola Normale Superiore, on April 17, 2019.